Pendampingan Kemandirian Keluarga dalam Merawat Lansia di Dusun Candirejo Desa Awang-awang Kecamatan Mojosari Mojokerto - Andriyanto, Arief; Kusumaningrum, Umi Azizah; Sajidin, Muhammad; Wicaksono, Arif (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
The main focus of the community service program this time is fostering and increasing family independence in caring for the elderly. Elderly families are expected to be able to increase family independence in caring for the elderly at home. The first method of implementing the program using the